1983
DOI: 10.1016/0020-7292(83)90024-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological observations of thrombo‐embolic disease during pregnancy and in the puerperium, in 56,022 women

Abstract: During a 28-year period the incidence of thrombosis and pulmonary embolism (TE) in pregnancy remained practically equal (0.7%), the incidence of puerperal TE was higher (2.3%) but decreased during the last 7 years. Puerperal TE was influenced by age, mode of delivery, hypertension and prophylactic anticoagulant therapy. TE during pregnancy was not noticeably correlated with age and hypertension. TE during pregnancy and in the puerperium are closely related diseases, but their epidemiological characteristics ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 5 publications
3
40
0
5
Order By: Relevance
“…Previous estimates have put the incidence of venous thromboembolism following caesarean section as being between 2.5 13 and 20 16 times that succeeding spontaneous vaginal deliveries, and this study found a four times increase in crude incidence. Arti®cial feeding at time of discharge carried greater risk of venous thromboembolism than breastfeeding.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Previous estimates have put the incidence of venous thromboembolism following caesarean section as being between 2.5 13 and 20 16 times that succeeding spontaneous vaginal deliveries, and this study found a four times increase in crude incidence. Arti®cial feeding at time of discharge carried greater risk of venous thromboembolism than breastfeeding.…”
Section: Discussionsupporting
confidence: 54%
“…Parity was not found to be a signi®cant factor for venous thromboembolism risk in this study. However, this factor has previously been found not to contribute independently, but to correlate with increasing age 16 .…”
Section: Discussionmentioning
confidence: 77%
“…Os principais fatores de risco para eventos tromboembólicos na gestação e puerpério são idade maior que 30 ou 35 anos 2,5,6,16,18,20,21 , multiparidade 2,5,18,21 , cesariana (principalmente se de urgência) 2,[5][6][7]16,18,[20][21][22] , hipertensão específica da gestação [5][6][7]21 , diabetes gestacional 5 , obesidade 2,4,6,7,[18][19][20]22 , hiperemese gravídica 6 , história pessoal ou familiar de trombose [2][3][4][5]18 , hemorragia pós-parto 2,[5][6][7]22 , anemia falciforme 2,4,19 , lúpus eritematoso sistêmico 4 , infecções ou internações na gravidez 5,6 , trabalho de parto prematuro …”
Section: Discussionunclassified
“…O padrão ouro para o diagnóstico é a venografia, pouco utilizada por ser exame invasivo e expor a paciente a radiação e contraste iodado 11,13 . Pacientes de alto risco, principalmente as que têm mais de um fator de risco, devem receber profilaxia ante e pós-natal 1,2,17,21 . A profilaxia antenatal deve ser realizada de preferência com heparina de baixo peso molecular subcutânea, sendo os benefícios sobre a não facionada: menor risco de trombocitopenia tipo II, pode ser utilizada em dose única diária e menor risco de indução a osteoporose e alergias 3,4,21,27,28 .…”
Section: Discussionunclassified
See 1 more Smart Citation